Determinación del peso vivo de la Cabra Chusca Lojana a través de la relación edad-cronometría dentaria en el cantón Zapotillo de la provincia de Loja - Jiménez Capa, Stalin Geovanny (2020)
In this research, a table of dental chronometry divided into three categories was developed: from birth to one year of age; from one year of age to 2 years; and, from 2 years onwards, the live weight was also identified in each category by developing a growth curve in males and females. 154 Chusca breed UEs distributed in 14 age categories were used to facilitate their study. The incisor teeth were identified in each UE and the age was calculated according to the type of tooth (deciduous or permanent), number of teeth present and according to the wear trait, and finally each animal was weighed. The field information was analyzed and tabulated, resulting in no incisor teeth in the first category at birth, at three months they already have a full mouth, wear occurs from 7 months and from 10 to 12 months it begins change from deciduous to permanent forceps; In the second category, the clamps are already complete, the 1 ° M begins to sprout from 18 months and at 2 years they are still growing; in the third category, at 30 months 1 ° M are complete, at 42 months the 2 ° M are complete and at 54 months the denture is completed with the ends and the incisor wear begins. While the live weight at birth is 2.3 kg; 3 to 4 months (weaning time) 9 and 11 kg; at one year of age 27.9 kg; at 2 years of 33.9 kg; 3 years of 43.4 kg, and then in the following years reach weights that range from 45.2 kg (4 years of age) to 47.9 kg (7 years of age). It is concluded that the Chusca goat presents the birth and development of its incisor teeth somewhat late compared to the bibliography consulted and that the greatest increase in live weight occurs at the first year of age despite the little technical and extensive management they receive. Key words: Chusca goat; dental chronometry; live weight; teeth.